THE EXISTENCE OF WOMEN'S LEADERSHIP IN CAMPUS ORGANIZATIONS - Azizah musdhalifah; Jawatir Pardosi; Nur Fitri Hndayani; Wingkolatin (SOSIOEDUKASI, 2025)
The pros and cons of women's leadership in Indonesia are interesting things that are still discussed by everyone. The strong stereotype of leaders who must come from the male gender who is more assertive and strong makes the existence of female leaders considered underestimated in society. This study uses a qualitative data approach method and descriptive analysis of secondary data sources obtained from various documents and news sources from web pages. The result of this study is that gender has no effect on a person's leadership.